Analisis Pengaruh Kepemimpinan Melayani, Budaya Organisasi, Kepercayaan Kepada Pimpinan Terhadap Kinerja Dosen Perguruan Tinggi Kristen - Purba, Enricho Fiktorando; Purba, Sukarman (Jurnal Manajemen Pendidikan Kristen, 2023)
The lecturer performance is a key variable for improving the quality of a higher education. Therefore, it is vital to examine what variables can affect the performance of lecturers either directly or indirectly. The aim of this research is to examine whether the organizational culture, servant leadership, trust have a direct and significant influence on the performance of the lecturer. The data was analyzed using the SEM-PLS model using the smartPLS 4.0 application software. The results of the research showed that there was no direct significant influence of Organizational Culture on the performance of the lecturer, p-value = 0.909; no direct impact of confidence on the performances of the faculty, p - value = 1.83; however, Servant Leadership has a significant direct influence on lecturers' performance, p – value = 0,000. Furthermore, it was found that there is no indirect impact of the Organizational Culture and Servant Leadership on the lecturers’ performance mediated by the trust, p– value = 0.183. In other words, based on this research, Servant Leadership is the only variable affects the performance of the lecturer at IAKN Tarutung